Tagore’s Religious Tolerance and Universal Unity Paradigm in the Era of Globalization - Nuridinov Javohir Izomovichs (Pubmedia Social Sciences and Humanities, 2025)
This article examines Rabindranath Tagore’s philosophy of religious tolerance and universal human unity as a normative framework for an age of globalization marked by intensified interdependence, pluralization of faiths, and rising extremism. Through close readings of Sadhana, The Religion of Man, Gitanjali, and Nationalism, it reconstructs Tagore’s “religion of the heart,” his Vedantic claim that outward creeds are secondary to an inner spiritual harmony, and his conviction that humanity shares a single moral root. The study situates these ideas within Tagore’s practical pedagogy at Santiniketan/Visva-Bharati and his critique of aggressive nationalism in favor of global citizenship. It then maps convergences with contemporary agendas—UNESCO’s intercultural and interfaith initiatives, the UN’s World Interfaith Harmony Week, the Sustainable Development Goals, and recent policy advances promoting enlightenment and religious tolerance—highlighting implications for education, media literacy, interreligious dialogue, and peacebuilding. The article argues that Tagore’s synthesis of Eastern (Vedantic) and Western humanist traditions, his ethic of love and compassion, and his human–nature concord offer actionable guidance for cultivating a culture of tolerance, inclusive civic identity, and ecological responsibility. It concludes that Tagore is not merely a historical voice but a living resource for renewing universal human solidarity amid digital fragmentation and ecological risk in the twenty-first century.